Reducing Lost Glass with PDCA Method at PT XYZ - Asep, Asep; Syaifullah, Agus Muhammad; Dahlia, Santi; Kinasih, Sekar; Prastyo, Yudi (Lentera Ilmu Nusantara, 2024)
PT XYZ is a glass manufacturing company with a production efficiency target of 83%. However, the high level of glass loss, especially in the IS Forming process in the C2.4 production line, hindered the achievement of this target. By using the PDCA (Plan, Do, Check, Action) method, this study aims to reduce glass loss caused by the Invert-Revert Center Line Problem. Remedial measures include root cause analysis, resetting technical parameters, and implementing specific solutions such as dummy settings, plunger timing settings, and cooling pressure optimization. From this PDCA approach, there was a significant decrease in glass loss from 173.37 tons to 71.05 tons, or by 59%. This implementation not only improves production efficiency but also provides cost savings. This study shows that the PDCA approach is effective in identifying and solving production problems, so that it can be applied to similar cases in other industrial sectors.